Mangroves and seascape connectivity: Identifying the next steps for research and management - L.G. Gillis; K. Arkema; S.Y. Chee; D.A. Hortua; M. Huxham; A.C. Moore; I. Nagelkerken; A. Ostrowski; D.J. Owino Omollo; M.L. Vozzo (Estuarine, Coastal and Shelf Science, 2026)

Global invasion dynamics of the charru mussel Mytella strigata (Hanley, 1843): mechanisms, impacts, knowledge gaps, and biosecurity implications - Paravanparambil Rajakumar Jayachandran; Pei-Zhen Ma; Marcel Velásquez; Broc S. Kokesh; Mantodi Jima; Kaent Immanuel N. Uba; César Lodeiros; Naduvilakkandy Vishnudattan; Luiza Costa Mello; Rafael Metri; Pablo Damian Borges Guilherme; Pablo Muniz; et al. (Hydrobiologia, 2026)

Aqueous acid washing as an effective pretreatment strategy for crude algal oil refining: Enrichment of fatty matter and reduction of impurities - Camille Zhi Qing P'ng; Mun Yuen Chang; Siti Hanifah Adiiba; Sheau Chien Chee; Noorazlenawati Borhan; Mohammad Ghadaffi Mohd Nor; Tg M. Uzaini Tg Mat; Cher Pin Song; Eng-Seng Chan (Algal Research, 2026)

Comparative analysis of deep learning methods for high-resolution satellite remote sensing image classification - Ejaz Ul Haq; Fung Fung Ting; Raphael C. -W. Phan; Mansour Almazroui; Rasha M. Abou Samra; Chee-Ming Ting (Modeling Earth Systems and Environment, 2026)

Critical habitats for sharks and rays in Asia remain largely unprotected - Adriana Gonzalez-Pestana; Peter M. Kyne; Emiliano García-Rodríguez; Ryan Charles; Vanessa Bettcher Brito; Asia O. Armstrong; Amanda Batlle-Morera; Marta D. Palacios; Christoph A. Rohner; Giuseppe Notarbartolo di Sciara; Jo Marie V. Acebes; Serena Adam; et al. (Biodiversity and Conservation, 2026)
The Asia region harbors exceptional chondrichthyan (shark, ray, and chimaera) diversity but faces intense fishing pressure. The Important Shark and Ray Areas (ISRA) process provides a collaborative, evidence-based framework to identify critical habitats and inform spatial management. We assessed ISRAs across the Bay of Bengal, Southeast Asia, and the Northwest Pacific to characterize their extent, ecological significance, and conservation relevance. We delineated 122 ISRAs spanning ~ 1 million km 2 (~ 3% of the region) across 12 jurisdictions and international waters, encompassing habitats for 121 species (~ 30% of Asia’s chondrichthyans), 76% of which are threatened. Depleted taxa (e.g., giant guitarfishes, Glaucostegidae) were represented, but charismatic megafauna (e.g., Whale Shark Rhincodon typus ) were overrepresented. In contrast, deepwater and freshwater species were underrepresented. Reproductive Areas were the most common ISRA sub-criterion applied (52% of ISRAs), largely in nearshore zones, while areas for range-restricted species were less frequently (18%) identified. Twelve ISRAs overlapped with biodiversity hotspots, including seven in areas of high overall chondrichthyan species richness and five in areas of high range-restricted species richness. Citizen science was the predominant research method used to delineate ISRAs, while fisheries data were underused despite the region’s major fisheries footprint. Geographic coverage was uneven: Indonesia held the most ISRAs (n = 40; 71.7% of ISRA coverage) while eight jurisdictions (e.g., Viet Nam, China, Republic of Korea) lacked ISRAs due to data gaps. Protection shortfalls are stark: MPAs cover

Micro‐Refuges or Ecological Traps: Context‐Dependent Effects of Rock Pools on Intertidal Biodiversity Across Latitudes - Louise B. Firth; Andrea Desiderato; Antony M. Knights; J. David Aguirre; Juan C. Astudillo; Juan C. Azofeifa‐Solano; David T. Bilton; Su Yin Chee; Hartvig C. Christie; Ronaldo A. Christofoletti; Amelia Curd; Katherine A. Dafforn; et al. (Global Ecology and Biogeography, 2026)
Aim We investigated how local‐scale environmental heterogeneity influences biodiversity patterns across broad biogeographic gradients, using intertidal microhabitats as a model system within one of the most environmentally stressful ecosystems on Earth. Location Intertidal habitats at 26 locations (two rocky shore sites per location) across six continents, spanning 98° of latitude (38°S to 60°N). Time Period 2019–2022. Major Taxa Studied Algae, sessile and mobile invertebrates. Methods We compared biodiversity and thermal environments across contrasting microhabitats (rock pools and adjacent emergent rock) along a latitudinal gradient, sampling during environmentally ‘milder’ and ‘harsher’ periods. Biodiversity was quantified using multiple richness metrics (mean, total, unique taxa) and functional diversity. Results Microhabitat differences strongly influenced biodiversity patterns across latitude. Rock pools consistently supported higher taxonomic and functional diversity than emergent rock, irrespective of sampling period, reflecting their ability to buffer thermal extremes, particularly under harsher conditions. Mean species richness exhibited a non‐linear, s‐shaped latitudinal pattern, with lowest values near the equator and higher richness at mid‐latitudes, diverging from classical Latitudinal Diversity Gradient expectations. Biodiversity differences between microhabitats were greatest in temperate regions and diminished at low latitudes, where extreme conditions constrained diversity across habitats. Main Conclusions Local environmental heterogeneity can substantially modify, and in some cases obscure large‐scale biodiversity patterns. By mediating exposure to environmental stress, intertidal microhabitats provide insight into how fine‐scale variability interacts with latitudinal stress gradients to shape biodiversity distributions. Incorporating microhabitat variability into biogeographic frameworks is important for understanding global biodiversity patterns and predicting ecological responses to climate change.

From waste to feed: utilisation of defatted microalgae from biofuel production as an alternative protein source in Asian sea bass (Lates calcarifer) diet - Hasniyati Muin; Norhayati Zainorahim; Norhidayah Mohd Taufek; Azima Syafaini Japar; Noorazlenawati Borhan; Chee Sheau Chien; Hasrizal Abd Rahman; M Ghadaffi M Noh; Fatin Ali’a M. Bakri; Mohd Syazwan Mohd Shukor; Wan Abd Al Qadr Imad Wan-Mohtar (Aquaculture International, 2025)

Development of a spatiotemporally integrated per-recruit model for Southern Flounder in the northern Gulf of America - Calvin Chee; Patrick M. Graham; Robert T. Leaf (Fisheries Research, 2025)

Renoprotective and antihypertensive mechanism of action of Clinacanthus nutans bioactive polysaccharides by suppression of reactive oxygen species/ nuclear factor/ matrix metalloproteinase (ROS/NF-ΚB/MMP-9) and upregulation of endothelial nitric oxide synthase/nitric oxide (eNOS/NO) pathways - Tan Yong Chia; Chee-Yuen Gan; Pike-See Cheah; Vikneswaran Murugaiyah; Tabinda Fatima; Esraa M. Haji; Ali F. Almutairy; Sulaiman Mohammed Alnasser; Farhan K. Alswailmi; Ashfaq Ahmad (Journal of Molecular Histology, 2025)

Modelling climatic variable impacts on ground-level ozone in Malaysia using backward trajectory and Generative Additive Models - F. P. Chee; M. C.-G. Ooi; Y. J. Wong; J. Sentian; J. Dayou; M. T. Latif; J. H.-W. Chang (International Journal of Environmental Science and Technology, 2025)

Revolutionizing dye adsorption: amino functionalized Zeolitic Imidazole Framework-8 for effective methyl blue removal - D. N. Awang Chee; N. A. Kamaludin; M. S. Soffian; F. Z. Abdul Halim; M. A. Mohamed Amin (International Journal of Environmental Science and Technology, 2025)

General quasi-equilibrium multivalent binding model to study diverse and complex drug-receptor interactions of biologics - Chee M. Ng; Robert J. Bauer (Journal of Pharmacokinetics and Pharmacodynamics, 2024)

Target-mediated drug disposition model for drugs with N > 2 binding sites that bind to a target with one binding site - Leonid Gibiansky; Chee M. Ng; Ekaterina Gibiansky (Journal of Pharmacokinetics and Pharmacodynamics, 2024)

Population structure in Mixornis tit-babblers across Sunda Shelf matches interfluvia of paleo-rivers - Laura Marie Berman; Meng Yue Wu; Pratibha Baveja; Emilie Cros; Yong Chee Keita Sin; Dewi M. Prawiradilaga; Frank E. Rheindt (Molecular Phylogenetics and Evolution, 2024)

Five Dimensions of Needs for Help: The Efficacy of a Technology-Based Intervention Among Asian American Breast Cancer Survivors - Eun-Ok Im; Wonshik Chee; Sudeshna Paul; Mi-Young Choi; Seo Yun Kim; SeonAe Yeo; Connie M. Ulrich; Marilyn M. Schapira; Giang T. Nguyen; Salimah Meghani; Jun J. Mao; Grace Ma; et al. (Journal of Cancer Education, 2024)

Uncovering the magnitude of African pangolin poaching with extensive nanopore DNA genotyping of seized scales - Darren Yeo; Amy H. J. Chan; Kum Chew Hiong; Jasmine Ong; Jun Yuan Ng; Jie Min Lim; Wendy Zhang; Sara R. Lim; Charlene J. Fernandez; Anna M‐S. Wong; Benjamin P. Y‐H. Lee; Max D. Y. Khoo; et al. (Conservation Biology, 2024)
Trade in pangolins is illegal, and yet tons of their scales and products are seized at various ports. These large seizures are challenging to process and comprehensively genotype for upstream provenance tracing and species identification for prosecution. We implemented a scalable DNA barcoding pipeline in which rapid DNA extraction and MinION sequencing were used to genotype a substantial proportion of pangolin scales subsampled from 2 record shipments seized in Singapore in 2019 (37.5 t). We used reference sequences to match the scales to phylogeographical regions of origin. In total, we identified 2346 cytochrome b ( cytb ) barcodes of white‐bellied ( Phataginus tricuspis ) (from 1091 scales), black‐bellied ( Phataginus tetradactyla ) (227 scales), and giant ( Smutsia gigantea ) (1028 scales) pangolins. Haplotype diversity was higher for P. tricuspis scales (121 haplotypes, 66 novel) than that for P. tetradactyla (22 haplotypes, 15 novel) and S. gigantea (25 haplotypes, 21 novel) scales. Of the novel haplotypes, 74.2% were likely from western and west‐central Africa, suggesting potential resurgence of poaching and newly exploited populations in these regions. Our results illustrate the utility of extensively subsampling large seizures and outline an efficient molecular approach for rapid genetic screening that should be accessible to most forensic laboratories and enforcement agencies.

Phenotypic screening in Organ-on-a-Chip systems: a 1537 kinase inhibitor library screen on a 3D angiogenesis assay - Camilla Soragni; Karla Queiroz; Chee Ping Ng; Arthur Stok; Thomas Olivier; Dora Tzagkaraki; Jeroen Heijmans; Johnny Suijker; Sander P. M. de Ruiter; Aleksandra Olczyk; Marleen Bokkers; Frederik Schavemaker; et al. (Angiogenesis, 2024)
Modern drug development increasingly requires comprehensive models that can be utilized in the earliest stages of compound and target discovery. Here we report a phenotypic screening exercise in a high-throughput Organ-on-a-Chip setup. We assessed the inhibitory effect of 1537 protein kinase inhibitors in an angiogenesis assay. Over 4000 micro-vessels were grown under perfusion flow in microfluidic chips, exposed to a cocktail of pro-angiogenic factors and subsequently exposed to the respective kinase inhibitors. Efficacy of compounds was evaluated by reduced angiogenic sprouting, whereas reduced integrity of the main micro-vessel was taken as a measure for toxicity. The screen yielded 53 hits with high anti-angiogenicity and low toxicity, of which 44 were previously unassociated with angiogenic pathways. This study demonstrates that Organ-on-a-Chip models can be screened in high numbers to identify novel compounds and targets. This will ultimately reduce bias in early-stage drug development and increases probability to identify first in class compounds and targets for today’s intractable diseases.

Environment and shipping drive environmental DNA beta‐diversity among commercial ports - Jose Andrés; Paul Czechowski; Erin Grey; Mandana Saebi; Kara Andres; Christopher Brown; Nitesh Chawla; James J. Corbett; Rein Brys; Phillip Cassey; Nancy Correa; Marty R. Deveney; et al. (Molecular Ecology, 2023)
The spread of nonindigenous species by shipping is a large and growing global problem that harms coastal ecosystems and economies and may blur coastal biogeographical patterns. This study coupled eukaryotic environmental DNA (eDNA) metabarcoding with dissimilarity regression to test the hypothesis that ship‐borne species spread homogenizes port communities. We first collected and metabarcoded water samples from ports in Europe, Asia, Australia and the Americas. We then calculated community dissimilarities between port pairs and tested for effects of environmental dissimilarity, biogeographical region and four alternative measures of ship‐borne species transport risk. We predicted that higher shipping between ports would decrease community dissimilarity, that the effect of shipping would be small compared to that of environment dissimilarity and shared biogeography, and that more complex shipping risk metrics (which account for ballast water and stepping‐stone spread) would perform better. Consistent with our hypotheses, community dissimilarities increased significantly with environmental dissimilarity and, to a lesser extent, decreased with ship‐borne species transport risks, particularly if the ports had similar environments and stepping‐stone risks were considered. Unexpectedly, we found no clear effect of shared biogeography, and that risk metrics incorporating estimates of ballast discharge did not offer more explanatory power than simpler traffic‐based risks. Overall, we found that shipping homogenizes eukaryotic communities between ports in predictable ways, which could inform improvements in invasive species policy and management. We demonstrated the usefulness of eDNA metabarcoding and dissimilarity regression for disentangling the drivers of large‐scale biodiversity patterns. We conclude by outlining logistical considerations and recommendations for future studies using this approach.

In-depth peptidomic profile and molecular simulation studies on ACE-inhibitory peptides derived from probiotic fermented milk of different farm animals - Priti Mudgil; Chee-Yuen Gan; Mohd Affan Baig; Marwa Hamdi; Khaja Mohteshamuddin; José E. Aguilar-Toalá; Abraham M. Vidal-Limon; Andrea M. Liceaga; Sajid Maqsood (Food Research International, 2023)

A global analysis of avian island diversity–area relationships in the Anthropocene - Thomas J. Matthews; Joseph P. Wayman; Robert J. Whittaker; Pedro Cardoso; Julian P. Hume; Ferran Sayol; Konstantinos Proios; Thomas E. Martin; Benjamin Baiser; Paulo A. V. Borges; Yasuhiro Kubota; Luiz dos Anjos; et al. (Ecology Letters, 2023)
Research on island species–area relationships (ISAR) has expanded to incorporate functional (IFDAR) and phylogenetic (IPDAR) diversity. However, relative to the ISAR, we know little about IFDARs and IPDARs, and lack synthetic global analyses of variation in form of these three categories of island diversity–area relationship (IDAR). Here, we undertake the first comparative evaluation of IDARs at the global scale using 51 avian archipelagic data sets representing true and habitat islands. Using null models, we explore how richness‐corrected functional and phylogenetic diversity scale with island area. We also provide the largest global assessment of the impacts of species introductions and extinctions on the IDAR. Results show that increasing richness with area is the primary driver of the (non‐richness corrected) IPDAR and IFDAR for many data sets. However, for several archipelagos, richness‐corrected functional and phylogenetic diversity changes linearly with island area, suggesting that the dominant community assembly processes shift along the island area gradient. We also find that archipelagos with the steepest ISARs exhibit the biggest differences in slope between IDARs, indicating increased functional and phylogenetic redundancy on larger islands in these archipelagos. In several cases introduced species seem to have ‘re‐calibrated’ the IDARs such that they resemble the historic period prior to recent extinctions.

Embedded information of aerosol type, hygroscopicity and scattering enhancement factor revealed by the relationship between PM2.5 and aerosol optical depth - Kuo-En Chang; Ta-Chih Hsiao; Si-Chee Tsay; Tang-Huang Lin; Stephen M. Griffith; Chian-Yi Liu; Charles C.-K. Chou (Science of The Total Environment, 2023)

A review on the use of cellulose nanomaterials for wastewater remediation of heavy metal ions - T. Marimuthu; C. Y. Chee; N. M. N. Sulaiman (International Journal of Environmental Science and Technology, 2023)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

An overview of organic contaminants in indoor dust, their health impact, geographical distribution and recent extraction/analysis methods - Thennakoon M. Sampath U. Gunathilake; Yern Chee Ching; Kiwao Kadokami (Environmental Geochemistry and Health, 2022)

Corrections to: Interpreting lacustrine bulk sediment δ15N values using metagenomics in a tropical hypersaline lake system - Mingfei Chen; Jessica L. Conroy; Robert A. Sanford; Joanne C. Chee-Sanford; Lynn M. Connor (Journal of Paleolimnology, 2022)

Liposomal drug delivery system for anti-inflammatory treatment after cataract surgery: a phase I/II clinical trial - Chee Wai Wong; Edmund Wong; Josbert M. Metselaar; Gert Storm; Tina T. Wong (Drug Delivery and Translational Research, 2022)

Whole genome sequencing analysis of multidrug-resistant tuberculosis in Singapore, 2006–2018 - Cynthia B. E. Chee; Leo K. Y. Lim; Rick T. H. Ong; Li Hwei Sng; Li Yang Hsu; Vernon J. M. Lee; Yee Tang Wang (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

A Modified Hybrid Wald’s Approximation Method for Efficient Covariate Selection in Population Pharmacokinetic Analysis - Yixuan Zou; Fei Tang; Chee M. Ng (The AAPS Journal, 2021)

Interpreting lacustrine bulk sediment δ15N values using metagenomics in a tropical hypersaline lake system - Mingfei Chen; Jessica L. Conroy; Robert A. Sanford; Joanne C. Chee-Sanford; Lynn M. Connor (Journal of Paleolimnology, 2021)

A global analysis of complexity–biodiversity relationships on marine artificial structures - Elisabeth M. A. Strain; Peter D. Steinberg; Maria Vozzo; Emma L. Johnston; Marco Abbiati; Moises A. Aguilera; Laura Airoldi; J. David Aguirre; Gail Ashton; Maritina Bernardi; Paul Brooks; Benny K. K. Chan; et al. (Global Ecology and Biogeography, 2021)
Aim Topographic complexity is widely accepted as a key driver of biodiversity, but at the patch‐scale, complexity–biodiversity relationships may vary spatially and temporally according to the environmental stressors complexity mitigates, and the species richness and identity of potential colonists. Using a manipulative experiment, we assessed spatial variation in patch‐scale effects of complexity on intertidal biodiversity. Location 27 sites within 14 estuaries/bays distributed globally. Time period 2015–2017. Major taxa studied Functional groups of algae, sessile and mobile invertebrates. Methods Concrete tiles of differing complexity (flat; 2.5‐cm or 5‐cm complex) were affixed at low–high intertidal elevation on coastal defence structures, and the richness and abundance of the colonizing taxa were quantified after 12 months. Results The patch‐scale effects of complexity varied spatially and among functional groups. Complexity had neutral to positive effects on total, invertebrate and algal taxa richness, and invertebrate abundances. However, effects on the abundance of algae ranged from positive to negative, depending on location and functional group. The tidal elevation at which tiles were placed accounted for some variation. The total and invertebrate richness were greater at low or mid than at high intertidal elevations. Latitude was also an important source of spatial variation, with the effects of complexity on total richness and mobile mollusc abundance greatest at lower latitudes, whilst the cover of sessile invertebrates and sessile molluscs responded most strongly to complexity at higher latitudes. Conclusions After 12 months, patch‐scale relationships between biodiversity and habitat complexity were not universally positive. Instead, the relationship varied among functional groups and according to local abiotic and biotic conditions. This result challenges the assumption that effects of complexity on biodiversity are universally positive. The variable effect of complexity has ramifications for community and applied ecology, including eco‐engineering and restoration that seek to bolster biodiversity through the addition of complexity.

Biogeochemical attenuation of nitrate in a sandy subterranean estuary: Insights from two stable isotope approaches - Wei Wen Wong; Andrew Applegate; Seng Chee Poh; Perran L. M. Cook (Limnology and Oceanography, 2020)
The role of permeable sediments and subterranean estuaries as coastal nutrient filters is a question of key interest, particularly in areas with high nitrogen loadings. Here, we evaluated the effectiveness of a sandy subterranean estuary in cycling and removing nitrate using stable isotopes of N and O at natural (δ 15 N‐NO 3 − and δ 18 O‐NO 3 − ) and enriched levels ( 15 N). Isotopes were used in conjunction with flow through reactors under anoxic conditions to quantify (1) the overall enrichment factor ( 15 ε) of nitrate removal processes which was then applied to estimate the in situ percentage of nitrate removal within the subterranean estuary and (2) the potential rates of denitrification, dissimilatory nitrate reduction to ammonium, and anammox. We found that 15 ε varied between −24 and −34‰ and were positively correlated with nitrate concentrations and the percentage of organic carbon added to the sediments. Using these 15 ε values in a Rayleigh distillation model resulted in an estimated average of 34% ± 14% nitrate removal within the subterranean estuary, less than half of the percentage estimated using the nitrate‐salinity mixing model (66% ± 28%). Denitrification was the most dominant nitrate removal pathway within the subterranean estuary with potential rates among the highest denitrification rates reported for both permeable and cohesive sediments. The contribution of dissimilatory nitrate reduction to ammonium showed significant seasonal variation while the rates of anammox were consistent throughout the study. We suggest that the spatial shift of the subterranean estuary is the most likely explanation for the seasonal differences in the rates of denitrification and dissimilatory nitrate reduction to ammonium.

Electro-Stimulated Release of Poorly Water-Soluble Drug from Poly(Lactic Acid)/Carboxymethyl Cellulose/ZnO Nanocomposite Film - Thennakoon M. Sampath U. Gunathilake; Yern Chee Ching; Cheng Hock Chuah; Nguyen Dai Hai; Liou Nai-Shang (Pharmaceutical Research, 2020)

Simulation analysis of the future surface ozone in Malaysian region under representative concentration pathways (RCPs) emission scenarios - S. S. K. Kong; J. Sentian; M. T. Chuang; M. C. G. Ooi; F. P. Chee; J. H. W. Chang (International Journal of Environmental Science and Technology, 2019)

Correcting common misconceptions to inspire conservation action in urban environments - Kylie Soanes; Michael Sievers; Yung En Chee; Nicholas S. G. Williams; Manisha Bhardwaj; Adrian J. Marshall; Kirsten M. Parris (Conservation Biology, 2019)
Despite repeated calls to action, proposals for urban conservation are often met with surprise or scepticism. There remains a pervasive narrative in policy, practice, and the public psyche that urban environments, although useful for engaging people with nature or providing ecosystem services, are of little conservation value. We argue that the tendency to overlook the conservation value of urban environments stems from misconceptions about the ability of native species to persist within cities and towns and that this, in turn, hinders effective conservation action. However, recent scientific evidence shows that these assumptions do not always hold. Although it is generally true that increasing the size, quality, and connectivity of habitat patches will improve the probability that a species can persist, the inverse is not that small, degraded, or fragmented habitats found in urban environments are worthless. In light of these findings we propose updated messages that guide and inspire researchers, practitioners, and decision makers to undertake conservation action in urban environments: consider small spaces, recognize unconventional habitats, test creative solutions, and use science to minimize the impacts of future urban development.

Infection criteria, inoculum sources and splash dispersal pattern of Colletotrichum acutatum causing bitter rot of apple in New Zealand - K. R. Everett; I. P. S. Pushparajah; O. E. Timudo; A. Ah Chee; R. W. A. Scheper; P. W. Shaw; T. M. Spiers; J. T. Taylor; D. R. Wallis; P. N. Wood (European Journal of Plant Pathology, 2018)

Transcriptional responses of the marine green alga Micromonas pusilla and an infecting prasinovirus under different phosphate conditions - Charles Bachy; Christina J. Charlesworth; Amy M. Chan; Jan F. Finke; Chee‐Hong Wong; Chia‐Lin Wei; Sebastian Sudek; Maureen L. Coleman; Curtis A. Suttle; Alexandra Z. Worden (Environmental Microbiology, 2018)
Summary Prasinophytes are widespread marine algae for which responses to nutrient limitation and viral infection are not well understood. We studied the picoprasinophyte, Micromonas pusilla , grown under phosphate‐replete (0.65 ± 0.07 d −1 ) and 10‐fold lower (low)‐phosphate (0.11 ± 0.04 d −1 ) conditions, and infected by the phycodnavirus MpV‐SP1. Expression of 17% of Micromonas genes in uninfected cells differed by >1.5‐fold ( q

Betanodavirus : Dissection of the viral life cycle - C‐F Low; B Syarul Nataqain; H‐Y Chee; M Z H Rozaini; M Najiah (Journal of Fish Diseases, 2017)
Progressive research has been recently made in dissecting the molecular biology of Betanodavirus life cycle, the causative pathogen of viral encephalopathy and retinopathy in economic important marine fish species. Establishment of betanodavirus infectious clone allows the manipulation of virus genome for functional genomic study, which elucidates the biological event of the viral life cycle at molecular level. The betanodavirus strategizes its replication by expressing anti‐apoptosis/antinecrotic proteins to maintain the cell viability during early infection. Subsequently utilizes and controls the biological machinery of the infected cells for viral genome replication. Towards the late phase of infection, mass production of capsid protein for virion assembly induces the activation of host apoptosis pathway. It eventually leads to the cell lysis and death, which the lysis of cell contributes to the accomplishment of viral shedding that completes a viral life cycle. The recent efforts to dissect the entire betanodavirus life cycle are currently reviewed.

Streptococcus agalactiae outbreaks in cultured golden pomfret, Trachinotus blochii (Lacépède), in Singapore - S M Chong; W K Wong; W Y Lee; Z B Tan; Y H Tay; X H Teo; L D Chee; C J Fernandez (Journal of Fish Diseases, 2017)

Designing a Network of Coral Reef Marine Protected Areas in Hainan Island, South China - Guanqiong Ye; Jie Liu; Loke M. Chou; Jacob Chee; Chuxin Zang (Coastal Management, 2017)

Intratracheal Administration of Hyaluronan-Cisplatin Conjugate Nanoparticles Significantly Attenuates Lung Cancer Growth in Mice - Susumu Ishiguro; Shuang Cai; Deepthi Uppalapati; Katie Turner; Ti Zhang; Wai Chee Forrest; M. Laird Forrest; Masaaki Tamura (Pharmaceutical Research, 2016)

The Severity of Gliosis in Hippocampal Sclerosis Correlates with Pre-Operative Seizure Burden and Outcome After Temporal Lobectomy - Alexandra M. Johnson; Ella Sugo; Daniela Barreto; Chee-Chung Hiew; John A. Lawson; Anne M. Connolly; Ernest Somerville; Enisa Hasic; Annie ME Bye; Anne M Cunningham (Molecular Neurobiology, 2016)

QSAR, in silico docking and in vitro evaluation of chalcone derivatives as potential inhibitors for H1N1 virus neuraminidase - Marzieh Yaeghoobi; Neni Frimayanti; Chin Fei Chee; Kusaira K. Ikram; Belal O. Najjar; Sharifuddin M. Zain; Zanariah Abdullah; Habibah A. Wahab; Noorsaadah Abd. Rahman (Medicinal Chemistry Research, 2016)

Mechanism-Based Competitive Binding Model to Investigate the Effect of Neonatal Fc Receptor Binding Affinity on the Pharmacokinetic of Humanized Anti-VEGF Monoclonal IgG1 Antibody in Cynomolgus Monkey - Chee M. Ng; Paul J. Fielder; Jin Jin; Rong Deng (The AAPS Journal, 2016)

Identification of immune response‐related genes and signalling pathways in spleen of Vibrio parahaemolyticus ‐infected Epinephelus fuscoguttatus (Forskal) by next‐generation sequencing - C‐F Low; N S Mariana; A Maha; H‐Y Chee; M Y Fatimah (Journal of Fish Diseases, 2016)

Identification of a novel cyprinid herpesvirus 3 genotype detected in koi from the East Asian and South‐East Asian Regions - J Chen; D Chee; Y Wang; G Y Lim; S M Chong; Y N Lin; T Huangfu (Journal of Fish Diseases, 2015)
Cyprinid herpesvirus 3 (Cy HV ‐3) is a highly contagious virus that causes significant morbidity and mortality in common carp Cyprinus carpio L. and considered to be one of the most important pathogens of koi and common carp worldwide. Cyprinid herpesvirus 3 infected consignments imported from East Asian and South‐East Asian regions were identified during quarantine period in Singapore, and virus from a 2005 consignment was successfully isolated in koi fin cells. A combination of sequence analyses and duplex PCR were used to characterize 15 Cy HV ‐3 isolates detected in koi consignments between 2005 and 2011. Sequence analyses of the enlarged 9/5, SphI‐5 and TK gene regions identified both the Asian 1 ( n = 11) and European 4 ( n = 4) genotypes. Duplex PCR analysis of two variable marker regions between ORF 29 and ORF 30 (marker I) as well as ORF 133 and its upstream region (marker II ) revealed viruses of genotypes J (I ++ II + ), U/I (I −− II − ), an intermediate genotype (I ++ II − ) and a novel genotype, I ++ II +Δ , which was identified in viruses from seven different consignments. This novel genotype has a 13‐bp deletion in marker II , while maintaining the I ++ allele of marker I. The I ++ II +Δ genotype may have emerged from East Asian and South‐East Asian regions in recent years.

Non‐immune‐related genes and signalling pathways in spleen of Vibrio parahaemolyticus ‐infected Epinephelus fuscoguttatus (Forskal) - C‐F Low; N S Mariana; A Maha; H‐Y Chee; M Y Fatimah (Journal of Fish Diseases, 2015)

Semi-mechanistic Multiple-Analyte Pharmacokinetic Model for an Antibody-Drug-Conjugate in Cynomolgus Monkeys - Dan Lu; Jin Yan Jin; Sandhya Girish; Priya Agarwal; Dongwei Li; Saileta Prabhu; Randall C. Dere; Ola M. Saad; Denise Nazzal; Neelima Koppada; Saroja Ramanujan; Chee M. Ng (Pharmaceutical Research, 2015)

Isolation and Characterization of Circadian Clock Genes in the Biofuel Plant Pongamia (Millettia pinnata) - Harry P. Winarto; Lim Chee Liew; Peter M. Gresshoff; Paul T. Scott; Mohan B. Singh; Prem L. Bhalla (BioEnergy Research, 2015)

Experimental infection of brown‐marbled grouper, E pinephelus fuscoguttatus (Forskal), with V ibrio parahaemolyticus identifies parvalbumin beta‐2 subunit I, alpha‐2‐macroglobulin, nattectin and immunoglobulin light chain, differentially expressed in resistant grouper - C‐F Low; M Nor Shamsudin; M Abdullah; H‐Y Chee; M Aliyu‐Paiko (Journal of Fish Diseases, 2015)
The mechanisms through which brown‐marbled grouper accomplishes resistance to infection, particularly against Vibrios , are not yet fully understood. In this study, brown‐marbled grouper fingerlings were experimentally infected with Vibrio parahaemolyticus, to identify disease resistance grouper, and the serum proteome profiles were compared between resistant and susceptible candidates, via two‐dimensional gel electrophoresis (2‐ DE ). The results showed that putative parvalbumin beta‐2 subunit I, alpha‐2‐macroglobulin, nattectin and immunoglobulin light chain proteins were among proteins that significantly overexpressed in the resistant fish as compared to the susceptible group of fish, whereas apolipoprotein E and immunoglobulin light chain proteins were observed to be differentially overexpressed in the susceptible fish. Further analysis by peptide sequencing revealed that the immunoglobulin light chain proteins identified in the resistant and susceptible groups differed in amino acid composition. Taken together, the results demonstrated for the first time that putative parvalbumin beta‐2 subunit I, alpha‐2‐macroglobulin, nattectin and immunoglobulin light chain are among important proteins participating to effect disease resistance mechanism in fish and were overexpressed to function collectively to resist V. parahaemolyticus infection. Most of these molecules are mediators of immune response.

Putative apolipoprotein A‐I, natural killer cell enhancement factor and lysozyme g are involved in the early immune response of brown‐marbled grouper, Epinephelus fuscoguttatus, Forskal, to Vibrio alginolyticus - C‐F Low; M N Shamsudin; H‐Y Chee; M Aliyu‐Paiko; E S Idrus (Journal of Fish Diseases, 2014)
The gram‐negative bacterium, Vibrio alginolyticus , has frequently been identified as the pathogen responsible for the infectious disease called vibriosis. This disease is one of the major challenges facing brown‐marbled grouper aquaculture, causing fish farmers globally to suffer substantial economic losses. The objective of this study was to investigate the proteins involved in the immune response of brown‐marbled grouper fingerlings during their initial encounter with pathogenic organisms. To achieve this objective, a challenge experiment was performed, in which healthy brown‐marbled grouper fingerlings were divided into two groups. Fish in the treated group were subjected to intraperitoneal injection with an infectious dose of V. alginolyticus suspended in phosphate‐buffered saline ( PBS ), and those in the control group were injected with an equal volume of PBS . Blood samples were collected from a replicate number of fish from both groups at 4 h post‐challenge and analysed for immune response‐related serum proteins via two‐dimensional gel electrophoresis. The results showed that 14 protein spots were altered between the treated and control groups; these protein spots were further analysed to determine the identity of each protein via MALDI ‐ TOF / TOF . Among the altered proteins, three were clearly overexpressed in the treated group compared with the control; these were identified as putative apolipoprotein A‐I, natural killer cell enhancement factor and lysozyme g. Based on these results, these three highly expressed proteins participate in immune response‐related reactions during the initial exposure (4 h) of brown‐marbled grouper fingerling to V. alginolyticus infection.

The pathology of ‘scale drop syndrome’ in Asian seabass, Lates calcarifer Bloch, a first description - S Gibson‐Kueh; D Chee; J Chen; Y H Wang; S Tay; L N Leong; M L Ng; J B Jones; P K Nicholls; H W Ferguson (Journal of Fish Diseases, 2012)
This is the first pathological description of ‘scale drop syndrome’ (SDS) in Asian seabass, Lates calcarifer Bloch. Cumulative mortality was estimated at 40–50%. The vasculitis in all major organs including the skin and associated tissue necrosis was distinctive. The dermis overlying scale beds was often necrotic and associated with scale loss. Necrosis of splenic ellipsoids, renal glomeruli and choroid rete glands of eye were further hallmarks of a disease with systemic vascular involvement. The brain was not spared vascular damage, and the resulting multifocal encephalomalacia probably accounts for the spiral swimming behaviour in some affected fish. Other lesions included accentuated hepatic lobulation and gastric gland necrosis. Nuclear chromatin margination and karyolysis in hepatocytes, renal tubular epithelium and gastric and intestinal epithelium suggest specific targeting of cells. Basophilic cytoplasmic inclusions were present in spleen, kidney, liver, heart and choroid rete, but they were not prominent. Using transmission electron microscopy, two morphological forms of virions were observed: single‐ and double‐enveloped hexagonal virions. Based on size and morphology, these virions resemble iridovirus or herpesvirus. The cause of SDS is unknown, but the pathological changes, especially the vasculitis, suggest an infectious aetiology, possibly viral.

Sequencing and Utilization of the Gossypium Genomes - Andrew H. Paterson; Jun-kang Rong; Alan R. Gingle; Peng W. Chee; Elizabeth S. Dennis; Danny Llewellyn; Leon S. Dure; Candace Haigler; Gerald O. Myers; Daniel G. Peterson; Mehboob ur Rahman; Yusuf Zafar; et al. (Tropical Plant Biology, 2010)

Status of the USA cotton germplasm collection and crop vulnerability - T. P. Wallace; D. Bowman; B. T. Campbell; P. Chee; O. A. Gutierrez; R. J. Kohel; J. McCarty; G. Myers; R. Percy; F. Robinson; W. Smith; D. M. Stelly; et al. (Genetic Resources and Crop Evolution, 2009)

Quantitative T-cell interferon-gamma responses to Mycobacterium tuberculosis-specific antigens in active and latent tuberculosis - C. B. E. Chee; T. M. S. Barkham; K. W. KhinMar; S. H. Gan; Y. T. Wang (European Journal of Clinical Microbiology & Infectious Diseases, 2009)

The Role of Posture, Magnification, and Grip Force on Microscopic Accuracy - Basil Safwat; Eileen L. M. Su; Roger Gassert; Chee Leong Teo; Etienne Burdet (Annals of Biomedical Engineering, 2009)

Resistance exercise effects on blood glutathione status and plasma protein carbonyls: influence of partial vascular occlusion - A. H. Goldfarb; R. S. Garten; P. D. M. Chee; C. Cho; G. V. Reeves; D. B. Hollander; C. Thomas; K. S. Aboudehen; M. Francois; R. R. Kraemer (European Journal of Applied Physiology, 2008)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Rationale for Fixed Dosing of Pertuzumab in Cancer Patients Based on Population Pharmacokinetic Analysis - Chee M. Ng; Bert L. Lum; Veronica Gimenez; Steve Kelsey; David Allison (Pharmaceutical Research, 2006)

Pharmacokinetics/Pharmacodynamics of Nondepleting Anti-CD4 Monoclonal Antibody (TRX1) in Healthy Human Volunteers - Chee M. Ng; Eric Stefanich; Banmeet S. Anand; Paul J. Fielder; Louis Vaickus (Pharmaceutical Research, 2006)

Pharmacokinetic–Pharmacodynamic–Efficacy Analysis of Efalizumab in Patients with Moderate to Severe Psoriasis - Chee M. Ng; Amita Joshi; Russell L. Dedrick; Marvin R. Garovoy; Robert J. Bauer (Pharmaceutical Research, 2005)

Intragenic linkage disequilibrium structure of the human perilipin gene (PLIN) and haplotype association with increased obesity risk in a multiethnic Asian population - Lu Qi; E. Shyong Tai; Chee Eng Tan; Haiqing Shen; Suok Kai Chew; Andrew S. Greenberg; Dolores Corella; Jose M. Ordovas (Journal of Molecular Medicine, 2005)

Increased prevalence of CFTR mutations and variants and decreased chloride secretion in primary sclerosing cholangitis - Meredith M. Regan; Peter R. Durie; Julian Zielenski; Sunil Sheth; Julie C. Shea; Michele D. Bishop; Sanjiv Chopra; Emily Malmberg; Carolyn Walker; Ryan Ricci; Lap-Chee Tsui; Steven D. Freedman (Human Genetics, 2003)

New Methodology for Extraction of Total Metals from Macroalgae and Its Application to Selected Samples Collected in Pristine Zones from Baja California, Mexico - F. de Len-Chavira; M. A. Huerta-Diaz; A. Chee-Barragn (Bulletin of Environmental Contamination and Toxicology, 2003)

Fusion of coregistered cross-modality images using a temporally alternating display method - J. S. Lee; B. Kim; Y. Chee; C. Kwark; M. C. Lee; K. S. Park (Medical & Biological Engineering & Computing, 2000)

Rhizosphere bacteria enhance the accumulation of selenium and mercury in wetland plants - M. P. de Souza; C. P. A. Huang; N. Chee; N. Terry (Planta, 1999)

Mapping of a candidate region for susceptibility to inclusion body myositis in the human major histocompatibility complex - Chee Choy Kok; Emma J. Croager; Campbell S. Witt; Lynette Kiers; Frank L. Mastaglia; Lawrence J. Abraham; M. J. Garlepp (Immunogenetics, 1999)

Analysis of the human Sonic Hedgehog coding and promoter regions in sacral agenesis, triphalangeal thumb, and mirror polydactyly - F. R. Vargas; E. Roessler; Karin Gaudenz; E. Belloni; Alexander S. Whitehead; Peader N. Kirke; James L. Mills; George Hooper; Roger E. Stevenson; Isabel Cordeiro; Patricia Correia; Temis Felix; et al. (Human Genetics, 1998)

Cytogenetic rearrangements involving the loss of the Sonic Hedgehog gene at 7q36 cause holoprosencephaly - Erich Roessler; Deeann E. Ward; Karin Gaudenz; Elena Belloni; Steven W. Scherer; Dian Donnai; Jacqueline Siegel-Bartelt; Lap-Chee Tsui; M. Muenke (Human Genetics, 1997)

Microwave-Assisted Solvent Extraction of Air Particulates for the Determination of PAHs - K. K. Chee; M. K. Wong; H. K. Lee (Environmental Monitoring and Assessment, 1997)

Optimization of the Microwave-Assisted Solvent Extraction of Petroleum Hydrocarbons in Marine Sediment and Soil - K. K. Chee; M. K. Wong; H. K. Lee (Environmental Monitoring and Assessment, 1997)

Microbial reductive dechlorination of PCBs - James M. Tiedje; John F. Quensen; Joann Chee-Sanford; Joshua P. Schimel; Stephen A. Boyd (Biodegradation, 1993)

Cluster method for analysis of transmitted information in multivariate neuronal data - M. -N. Chee-Orts; L. M. Optican (Biological Cybernetics, 1993)